The use of the "vulnerability" concept in the nursing area La utilización del concepto "vulnerabilidad" por enfermería A utilização do conceito "vulnerabilidade" pela enfermagem - Lucia Yasuko Izumi Nichiata; Maria Rita Bertolozzi; Renata Ferreira Takahashi; Lislaine Aparecida Fracolli (Universidade de São Paulo, 2008)
The objective of this article was to briefly retrieve the meaning of the vulnerability concept, which has been used in the healthcare area; also, to discuss how it has been used in the Nursing area. Amidst several different focuses and objects, studies have been attempting to overcome the classical reasoning of risk in epidemiology, advancing towards the discussion of the social determinants for the production of health problems. Este artículo tuvo por objetivo hacer un breve rescate del concepto de vulnerabilidad que viene siendo utilizado en el área de la salud y discutir como viene siendo utilizado por la enfermería. Los estudios, en medio de la diversidad de enfoques y objetos, han buscado superar el raciocinio clásico de riesgo en epidemiología, avanzando para la discusión de los determinantes sociales en la producción de los agravantes de las enfermedades. Este artigo teve por objetivo realizar breve resgate do conceito de vulnerabilidade que vem sendo utilizado na área da saúde e discutir sua utilização pela enfermagem. Os estudos, em meio à diversidade de enfoques e objetos, têm buscado superar o raciocínio clássico de risco em epidemiologia, avançando para a discussão dos determinantes sociais na produção dos agravos.